ETIOLOGIC FACTORS AND CLINICAL EVALUATION OF RESTORED FRACTURED ANTERIOR TEETH: AN OBSERVATIONAL STUDY - Uzay KOÇ VURAL; Arlin KIREMITÇI; Saadet GÖKALP (Istanbul University, 2016)
Purpose: The aims of this study were to investigate the etiologic factors and to evaluate performance of composite resin on fractured crown in permanent anterior teeth at 6 and 12 months. Subjects and Methods: Records from 51 patients were retrieved from a Dental School Clinic, comprising 73 fractured anterior teeth directly restored with a submicron hybrid composite (Spectrum TPH) resin and respective adhesive system (Prime&Bond NT) were evaluated. The United States Public Health Service criteria were used to assess the clinical evaluation. Data were analyzed using the Wilcoxon Signed Rank, Kruskal-Wallis, Mann-Whitney U, and Siegel and Castellan tests. Results: Seventy-two maxillary incisors and one canine of 51 patients were evaluated. The patient's age at the time of therapy ranged from 14 to 64 years old (mean 25.47). Mostly observed crown fracture was seen in upper incisors (84.9%) and due to falls (58.8%). At the 6-month follow-up, one patient lost one restoration and at the 12-month, one patient lost one and one lost two restorations. A statistically significant difference was found in terms of marginal adaptation between 6 and 12 months. Conclusion: In this short-term observation period, remaining tooth structure was conserved and good patient compliance was achieved. Factors such as esthetic and/or cost should be considered to indicate the direct composite restorations.